Pengaruh Minyak Mentah dan Batubara terhadap Return Saham Perusahaan Pertambangan di Bursa Efek Indonesia - Hamzah, Hamzah (Universitas Darwan Ali, 2023)
This research aims to examine the influence of global crude oil and coal prices on the performance of the mining and metals sector on the Indonesia Stock Exchange (BEI). The research methodology used is descriptive with a quantitative approach. The population of this study includes 79 companies listed in the mining industry sector on the IDX. The research sample was selected using a technique called purposive sampling, and finally, a total of 22 companies were selected. Data collection was carried out using a documentation approach. The analysis results show that world crude oil and coal prices have a significant and positive effect on the stock returns of companies operating in the mining sector on the IDX, both partially and simultaneously. The results of the analysis show that there is a positive and significant influence of crude oil and coal prices on stock returns. Research makes an important contribution to understanding financial markets, especially those related to the mining sector, as a reference for decision-makers and stakeholders in managing risks and anticipating market changes.